Managing Soil Acidity for Crop Production in Sikkim: A Policy Options - Das, Shaon Kumar; Avasthe, R. K. (Indian Journal of Hill Farming, 2018)
Acidic soils create production problems by limiting the availability of some essential plant nutrients and increasing that of the soil solution's toxic elements, such as aluminium, iron and manganese, the major cause of poor crop performance and failure in acidic soils. In East Sikkim, 14.9 percent area is extremely acidic, 29.4 percent area is very strongly acidic, 28.7 percent area is strongly acidic, 18.3 percent area is moderately acidic and 6.5 percent area is slightly acidic in reaction. In North Sikkim, 9.3 percent area is extremely acidic, 18.5 percent very strongly acidic, 34.6 percent strongly acidic, 24.4 percent moderately acidic and 6.5 percent slightly acidic in reaction. In South Sikkim, 30.8 percent area is moderately acidic, 23.4 percent strongly acidic, 18.2 percent slightly acidic, 9.2 percent very strongly acidic and 4.4 percent extremely acidic in reaction. In West Sikkim, 38.9 percent area is moderately acidic, 32.3 percent strongly acidic, 14.2 percent slightly acidic, 9.0 percent very strongly acidic and 2.6 percent extremely acidic in reaction. Strongly to extremely acidic soils(pH